Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1249/mss.0000000000001155
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Exercise Intensity and Duration on Postexercise Executive Function

Abstract: The present findings showed that postexercise EF improvement could be prolonged after MI exercise with a moderate duration compared with volume-matched LI exercise with a longer duration. In addition, MI exercise with a relatively long duration may slightly prolong the postexercise EF improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 27 publications
6
77
1
1
Order By: Relevance
“…1A. Before the day of the experiment, the subjects performed the color-word Stroop task (CWST) (8) 10-15 times until the subject obtained consistent scores (19,22,24). Subsequently, their maximal workload (W max ) was determined to calculate the intensity required for the exercise protocols.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A. Before the day of the experiment, the subjects performed the color-word Stroop task (CWST) (8) 10-15 times until the subject obtained consistent scores (19,22,24). Subsequently, their maximal workload (W max ) was determined to calculate the intensity required for the exercise protocols.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, HIIE may sufficiently facilitate neuronal activation and excitation levels to an extent that summation is facilitated and cognitive performance is improved (20,23,24). Thus, highervolume exercise with sufficient intensity and duration (e.g., HIIE) effectively prolongs the exercise-induced, improved EF, as compared with volume-matched, moderate-intensity continued exercise (22,24). As mentioned, HIIE is emerging as an alternative to current health-related exercise guidelines (30), but the impact of HIIE on the cerebral vasculature (30) and implications for cognitive function have not been established.…”
Section: A-v Diff Lactate Vs Executive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, CWST focuses on selective attention to specific information and the IC of a prepotent response during decision-making tasks involving stimuli and responses [ 1 , 29 ]. The CWST in the present study was programmed by modifying an Excel Visual Basic for Applications, as described in our previous studies [ 12 15 ]. We measured both reaction time and response accuracy using the CWST as previously described [ 12 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that an acute bout of aerobic exercise can improve several aspects of EF, especially inhibitory control (IC), in various populations [ 8 15 ]. Moreover, previous studies demonstrated that aerobic exercise-induced improvement of IC was related to enhanced neural activity in the brain [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%